(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT This study aimed to find out how the performance of the Office of Religious Affairs in Minimizing underage marriage in Parangloe District. This study used a qualitative research with the type was descriptive research. It described a problem about level of underage marriage in Parangloe District. The results of this study conducted at the KUA Parangloe District showed there were 4 cases of underage marriage in Parangloe District recorded, of which 2 cases occurred in 2019 and 2020. For the Religious Affairs Office of Parangloe District in an effort to overcome and reduce the level of marriage in Parangloe District. Underage marriages in Parangloe District could be carried out by organizing activities or focusing on discussing underage marriage and socialization of the Marriage Law which was regularly and well programmed and organized as well as it need to collaborate with various institutions or mass organizations, both private and public. government to work together to tackle this problem. Keywords: Employee Performance, Religious Affairs Office, Underage Marriage.